THE CONCEPT OF “BENEFIT” AND “HARM” IN ENGLISH AND UZBEK LANGUAGES - Divanova Mohira Husanovna (Scholar Express Journal, 2025)
This article presents a comparative linguistic and cultural analysis of the concepts benefit and harm—rendered as foyda and zarar in the Uzbek language. The study examines their semantic fields, metaphorical extensions, phraseological patterns, and socio-pragmatic usage in English and Uzbek. Through descriptive, contrastive, and semantic analysis, the research highlights how each language encodes social, moral, and evaluative dimensions of these concepts. The findings demonstrate that while the universality of benefit and harm is shared across cultures, their linguistic expression varies greatly depending on cultural norms, social expectations, and communication traditions
Keywords: benefit; harm; foyda; zarar